A long road: Patterns and prospects for social equity, diversity, and inclusion in public administration. (8th March 2022) - McCandless, Sean; Bishu, Sebawit G.; Gómez Hernández, Melissa; Paredes Eraso, Érika; Sabharwal, Meghna; Santis, Esteban Leonardo; Yates, Sophie
Abstract: Public Administration, the field's oldest journal, is now 100 years old. Despite this centenary, it has only been relatively recently that scholars have examined questions of: (1) how diverse, equitable, and inclusive the field is; (2) how oppressive administrative structures marginalize groups; and (3) what principles of diversity, equity, and inclusion (DEI) mean globally. We seek to contribute to this conversation by reflecting on what is currently known about answers to these questions, especially from global perspectives. We do this by presenting five purposively selected vignettes, each on some dimension of DEI. We frame and analyze these vignettes using Gooden's "name, blame, and claim" framework. Reflections are offered regarding how the field can better center and achieve DEI.